Neuroprotective Effect of Melatonin Loaded in Human Serum Albumin Nanoparticles Applied Subconjunctivally in a Retinal Degeneration Animal Model - Martinez, Sofia Mickaela (2025)
AbstractBackground/objectives: Neurodegenerative ocular diseases, such as age-related macular degeneration (AMD) and glaucoma, represent growing public health concerns. Oxidative stress plays a key role in their development, damaging retinal cells and accelerating disease progression. Melatonin (Mel) is a potent antioxidant with neuroprotective properties; however, it faces limitations such as low solubility. This study proposes the use of human serum albumin nanoparticles (Np-HSA) to enhance the delivery of Mel to the posterior segment of the eye and evaluates its neuroprotective and anti-apoptotic effects on the retina.Methods: A model of retinal degeneration was induced in New Zealand albino rabbits using cytotoxic and oxidative agents. Np-HSA-Mel nanoparticles were administered subconjunctivally, and cellular viability and retinal functionality were assessed using flow cytometry and pupillary light reflex (PLR). Histological and immunohistochemical studies, including the TUNEL assay, were performed to analyse cell survival and apoptotic index.Results: Np-HSA-Mel significantly preserved pupillary function and cell viability, demonstrating lower apoptosis compared to Mel solution and Np-HSA alone. Histologically, eyes treated with Np-HSA-Mel exhibited fewer structural alterations and greater cellular organisation. The TUNEL assay confirmed a significant reduction in the apoptotic index of retinal ganglion cells (RGCs) treated with Np-HSA-Mel.Conclusions: Np-HSA-Mel effectively overcame ocular barriers, achieving greater neuroprotective efficacy at the retinal level. These findings highlight the synergistic potential of albumin and Mel in treating neurodegenerative ocular diseases, opening new perspectives for future therapies.